2004
DOI: 10.1128/jvi.78.5.2222-2231.2004
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of Interaction of INI1/hSNF5 with Retroviral Integrases and Its Functional Significance

Abstract: Integrase interactor 1 (INI1)/hSNF5 is a host factor that directly interacts with human immunodeficiency virus type 1 (HIV-1) integrase and is incorporated into HIV-1 virions. Here, we show that while INI1/hSNF5 is completely absent from purified microvesicular fractions, it is specifically incorporated into HIV-1 virions with an integrase-to-INI1/hSNF5 stoichiometry of approximately 2:1 (molar ratio). In addition, we show that INI1/hSNF5 is not incorporated into related primate lentiviral and murine retrovira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 51 publications
5
70
0
Order By: Relevance
“…Moreover, CA must also form interactions with a wide variety of host proteins (62)(63)(64). While IN forms critical interactions with LEDGF (65,66), as well as interactions with TRN-SR2(TNPO3) (35,67) and INI-1/hSNF5 (36,68), and also undergoes multimerization processes (21,(69)(70)(71), the larger number of specialized CA-CA interactions that mediate accurate virion assembly may make CA exceptionally fragile (Fig. 3A to E) (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, CA must also form interactions with a wide variety of host proteins (62)(63)(64). While IN forms critical interactions with LEDGF (65,66), as well as interactions with TRN-SR2(TNPO3) (35,67) and INI-1/hSNF5 (36,68), and also undergoes multimerization processes (21,(69)(70)(71), the larger number of specialized CA-CA interactions that mediate accurate virion assembly may make CA exceptionally fragile (Fig. 3A to E) (11).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, mutagenesis studies utilizing complementation have indicated the likelihood that IN forms a functional multimer (31)(32)(33). Other mutagenesis studies have also suggested a critical role for IN-binding cellular cofactors, for example, lens epithelium-derived growth factor (LEDGF) (34) and possibly transportin SR-2 (TRN-SR2, or TNPO3) (35) and integrase interactor (INI) 1/hSNF5 (36). Further work using scanning or site-directed mutagenesis has revealed individual IN amino acids that are likely to be involved in DNA binding or other critical IN functions (22,(37)(38)(39)(40)(41)(42)(43)(44).…”
mentioning
confidence: 99%
“…Lysine 4 and 9 of H3 are methylated at transcriptional start sites 15 and both H3 and H4 have varying acetylation patterns depending on whether they are in open reading frames or intergenic regions 16 Other chromosomal proteins also redistribute with transcription and at least one, the INI/SNF5 complex, has been shown to interact with HIV-1 integrase. 17 Any or all of these factors (and others) might affect integration site choice.…”
Section: What Guides the Integration Event?mentioning
confidence: 99%
“…4B, right). As described above, INI1/hSNF5 has been shown to be specifically encapsidated into HIV-1 virions, probably through the IN region of Gag-Pol (Yung et al, 2001(Yung et al, , 2004. In addition, a recent study demonstrates that the IN-INI1/hSNF1 interaction selectively recruits SAP18 and HDAC1, components of the Sin3a-HDAC complex, into the HIV-1 virion, increasing the infectivity of the virions (Sorin et al, 2009).…”
Section: Cellular Interactors Affecting On Postintegration Stepsmentioning
confidence: 99%
“…Moreover, expression of the S6 fragment in Jurkat T cells protected the cells against HIV-1 replication (Yung et al, 2001). Although this inhibitory effect was not detected in full-length INI1/hSNF5, the WT INI1/hSNF5 has been shown to be incorporated into virions during virus production (Yung et al, 2001;Yung et al, 2004). Given the recent report that depletion of endogenous INI1/hSNF5 did not affect the transduction efficiency of an HIV-1-based vector, this suggests that INI1/hSNF5 is likely implicated in post-integration steps, rather than the integration step as we shall see below, particularly in HIV-1 production (Ariumi et al, 2006).…”
Section: Cellular Interactors Affecting On Integration Stepmentioning
confidence: 99%